The Role of Human Resource Competence in Supporting the Performance of Public Sector Organizations in Palu City - Syahruddin Hattab; Daswati Daswati; Mario Beldwin Iglesias Padjalo; Nurul Izmi Humairsh (Program Pascasarjana Universitas Negeri Makassar, 2023)
This research originates from the role of human resource competence within an institution being crucial, as it acts as the driving force and manager of the system. To ensure smooth functioning, its handling must consider important aspects such as training, development, and motivation. The purpose of this research is to understand the role of human resource competence in supporting the performance of the public sector organization. The objectives of this research are (1) to understand and analyze the Role of Human Resource Competence in Supporting the Performance of Public Sector Organizations in Palu City. The qualitative method, which is based on data and information from informants using a phenomenological pattern, was employed. The research findings indicate that both supportive and hindering factors play a crucial role in the development of human resource competence in the public sector of Palu City. There is a positive impact of training access, management support, and performance assessment on employee motivation. However, hindering factors such as excessive workload, dynamic demands, and limited access to new information can constrain competence development efforts due to the rapid changes in the public sector environment.